Adapting to Smoke-Free Psychiatric Care: An Audit of Patient Behaviour, Medication Management, and Staff Challenges - Praveen Kumar; Caio Bezzerraculas; Ananya Santosh; Nikki Thomson (BJPsych Open)
Aims: The audit conducted at New Craig’s Psychiatric Hospital’s Intensive Psychiatric Care Unit (IPCU) aimed to evaluate the impact of the Smoke-Free Perimeter Law on patient care and staff well-being. It sought to understand how the law affected patient behaviour and health, particularly for those on medications like clozapine, and to assess the changes in staff workload and safety. The study also aimed to identify the operational challenges and necessary adaptations in the IPCU following the law’s implementation.